Measurement of interfacial tension in melts of polymer blends - A. N. Matvienko; Yu. P. Miroshnikov (Тонкие химические технологии, 2006)
The apparatus construction and primary techniques used on measurements of surface and interfacial tensions in high-viscous polymer melts has been examined. This method is based on spinning drop theory by Vonnegut. Measured values of surface and interfacial tensions for several polymer systems show good correlation with corresponding data from literature. Relative error of the measurements was in the range of 2-8%